Adenoid Cystic Carcinoma: A Case Report - Hossen, Iqbal; Chowdhury, Farid Hossain; Shil, Niloy Ananda; Qader Mirza, Md Aminul; Chowdhury, M Alamgir; Ullah, Md Kalim (Eastern Medical College Journal, 2022)
A 52-year-old male patient attended on 13 July 2022 with the complaints of pain in right ear and voice change for 1 month and cough for 15 days, difficulty in swallowing along with weight loss for same duration of past 1 month. Examination revealed a swelling on the right side of neck over the submandibular region also with cervical lymphadenopathy (level IB). After all evaluation, all biochemical tests were normal, but Fiber Optic Laryngoscopy (FOL) revealed right vocal cord palsy, USG of neck revealed right submandibular mass and cervical lymphadenopathy, CT scan of Neck up to Mid-chest revealed no pathology and last but not the least pre-operative FNAC was done and revealed organizing abscess. After that patient underwent excision of the right sub mandibular mass and removal of few superficial group of lymph nodes. Post-operative histopathology revealed Adenoid Cystic Carcinoma (ACC). Patient presented to us with no complain about submandibular gland or fine needle aspiration cytology (FNAC) also doesn’t indicate about malignancy, but our clinical suspicion was submandibular gland malignancy, that’s why we have decided to publish this case report. After operation Patient was fine till his last follow-up. Eastern Med Coll J. Jan 2023; 8 (1) 28-30